2022
DOI: 10.4274/balkanmedj.galenos.2022.2021-8-131
|View full text |Cite
|
Sign up to set email alerts
|

Anti-SARS-CoV-2 IgG and Neutralizing Antibody Levels in Patients with Past COVID-19 Infection: A Longitudinal Study

Abstract: Background: Monitoring the longevity of immunoglobulin G (IgG) responses following severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infections is vital to understanding the role of antibodies in preventing infection. Aims: To determine the quantitative IgG responses specific to the Spike-S1 (S1) receptor-binding domain (S1/RBD) region of the virus in serum samples taken between 4 weeks and 7 months after polymerase chain reaction (PCR) positivity in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Monitoring SARS-CoV-2 antibodies in the host is essential for determining the significance of these antibodies in avoiding illness and revising vaccination policy [ 11 ]. Therefore, determining the changes in anti-S-RBD antibody and surrogate neutralizing antibody (snAb) levels in healthy persons before and after the third BNT162b2 vaccination (on the 15th, 60th, and 90th days) was the focus of our investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Monitoring SARS-CoV-2 antibodies in the host is essential for determining the significance of these antibodies in avoiding illness and revising vaccination policy [ 11 ]. Therefore, determining the changes in anti-S-RBD antibody and surrogate neutralizing antibody (snAb) levels in healthy persons before and after the third BNT162b2 vaccination (on the 15th, 60th, and 90th days) was the focus of our investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Tests with a nAb IH% ≥35% were regarded as positive, and tests with a nAb IH% <20% were deemed negative. According to the manufacturer’s instructions, nAb IH% between 20% and 35% was deemed borderline [ 10 , 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…Antibodies and memory B cells are considered correlates of protection against various viral infections [ 29 ]. However, anti-SARS-CoV-2 IgG antibodies may not be serving the purpose as evident from the reports of reinfection in seropositive recovered/ breakthrough infections [ 30 , 31 ]. A lack of correlation between anti-IgG antibody levels against an antigen and the percentages of CD4 + naive T cells could be related to different types of immune responses generated and also to the factors responsible for the complexity of the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in the group with underlying diseases, the patients were older and had a lower proportion of vaccinated patients when compared with the group of patients without underlying diseases. Anti-CoV IgG is a protective IgG that is capable of adhering to the virus and preventing it from entering the host cell ( Dinc et al, 2022 ). Vaccination is the most effective way to boost the levels of anti-CoV IgG, and our results showed that patients with underlying disease are older and less vaccinated, indicating that age and underlying disease are factors influencing the symptomatic patients and long total disease course in re-positive patients.…”
Section: Discussionmentioning
confidence: 99%